2017
DOI: 10.1002/smtd.201700230
|View full text |Cite
|
Sign up to set email alerts
|

Recent Smart Methods for Achieving High‐Energy Asymmetric Supercapacitors

Abstract: With the development of portable electronic equipment, electric vehicle, space technology, and power‐grid and energy‐storage technology, new efficient energy‐storage devices need to be developed urgently. Recently, asymmetric supercapacitors (ASCs) have attracted ever‐increasing interest as one of the most promising energy‐storage devices given their remarkable advantages of wide operation voltage window, high power density, and moderate energy density. However, to meet the needs of the rapid development of el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
78
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 161 publications
(78 citation statements)
references
References 159 publications
(209 reference statements)
0
78
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8] As one of the most promising energy storage devices, aqueous zinc-ion batteries (ZIBs) has gained ever-increasing attention on account of its outstanding safety, high theoretical capacity (Zn: ≈820 mAh g −1 ), low cost as well as environmental benignity. [1][2][3][4][5][6][7][8] As one of the most promising energy storage devices, aqueous zinc-ion batteries (ZIBs) has gained ever-increasing attention on account of its outstanding safety, high theoretical capacity (Zn: ≈820 mAh g −1 ), low cost as well as environmental benignity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8] As one of the most promising energy storage devices, aqueous zinc-ion batteries (ZIBs) has gained ever-increasing attention on account of its outstanding safety, high theoretical capacity (Zn: ≈820 mAh g −1 ), low cost as well as environmental benignity. [1][2][3][4][5][6][7][8] As one of the most promising energy storage devices, aqueous zinc-ion batteries (ZIBs) has gained ever-increasing attention on account of its outstanding safety, high theoretical capacity (Zn: ≈820 mAh g −1 ), low cost as well as environmental benignity.…”
Section: Introductionmentioning
confidence: 99%
“…[13,[34][35][36][37] In previous studies, MoO 3 has shown its reversible Li-ion insertion/extraction ability. [13,[34][35][36][37] In previous studies, MoO 3 has shown its reversible Li-ion insertion/extraction ability.…”
Section: Introductionmentioning
confidence: 99%
“…[15] Such materials are not rare, including but not limited in carbon nanotubes, graphene, activated carbon (AC), mesoporous carbon, etc. [15] Such materials are not rare, including but not limited in carbon nanotubes, graphene, activated carbon (AC), mesoporous carbon, etc.…”
mentioning
confidence: 99%
“…It can be easily induced into TMOs through annealing at certain temperatures in oxygen‐deficient atmosphere (vacuum, Nitrogen, Argon, etc .) or reducing atmosphere (hydrogen or ammonia) . Recently, Zhang et al .…”
Section: Recently Emerging Approaches For Surface Engineeringmentioning
confidence: 99%